What Causes Firms to Hide Output? : The Determinants of Informality - Inchauste, Gabriela (IMF Working Papers; Working Paper ;, 2005)
In many developing countries, a significant part of economic activity takes place in the informal sector. Earlier work has examined the determinants of the size of the informal sector, focusing separately on factors such as tax and regulation burden, financial market development, and the quality of the legal system. We revisit this issue by using an integrated dataset which contains rich information on all these aspects. Testing the channels affecting the degree of informality, we find evidence that all previously identified factors indeed play a role in driving informality. In particular, and consistent with the suggested theoretical model, we find support for the significance of the quality of the legal system.